A new immunofluorescence determination of Parkinson's disease biomarkers using silver nanoparticles - Chao Qin; Jun Xia; Yong Wen; Jun Wang; Chen Zhong (Alexandria Engineering Journal)
Parkinson's disease (PD) is a neurodegenerative condition marked by a steady loss of dopaminergic neurons in the brain's substantia nigra. Prompt identification and tracking of PD progression are essential for prompt intervention and efficient PD care. In this study, we developed an immunofluorescence detection approach for α-synuclein (α-syn), a critical biomarker associated with PD, that is both extremely sensitive and specific. Using polyethylene glycol (PEG)-functionalized magnetic beads (MBs) and an Ag+ fluorescence probe (Ag+-FP) based on Rhodamine 6 G, the suggested method makes use of an immunofluorescence detection system. The system's workings are based on antigen-antibody complexes. Identified as Ab1-MBs@α-syn@Ab2-Ag NPs, the immuno-complexes encapsulate α-synuclein between anti-α-synuclein antibodies (Ab1) fixed on amino-MBs and Ag Nanoparticles functionalized with matching Ab2. α-synuclein detection was accomplished at a limit of less than 8 pg/mL through optimization of pH, reaction duration, and antibody concentration. The method showed very little cross-reactivity with other widely used biomarkers and a high specificity. The system showed a linear range of 524.8 ng/mL to 0.2 ng/mL. The results, which showed recovery values ranging from 97.00 % to 99.57 % and were consistent with those obtained using a commercial ELISA kit, indicated the system's potential for clinical applications in the diagnosis and monitoring of PD.